Fire-safe Distance Between Ro-Ro Space Openings and Life-saving Appliances - Pierrick Mindykowski (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
As part of the FIRESAFE II project commissioned by the European Maritime Safety Agency a study was performed to determine a safe distance between side openings and Life-Saving Appliances (LSA) in ro-ro spaces to keep them available and usable for evacuation. The study utilised analytical calculations and CFD simulations. Two exclusion zones, where LSA should not be placed, were defined. The first zone relates to LSA within an embarkation station and includes the full vertical side of the ship, 6 metres forward and aft the opening. The second zone, without presence of passengers, consisted of the exclusion zone extending 6 metres around the opening. The results presented in the paper have been implemented in the International Maritime Organization interim guidelines for minimising the incidence and consequence of fires in ro-ro spaces and special category spaces of new and existing ro-ro passenger ships.